THE RELATIVE WAVELENGTH INDEPENDENCE OF IR LAGS IN ACTIVE GALACTIC NUCLEI: IMPLICATIONS FOR THE DISTRIBUTION OF THE HOT DUST - Oknyansky, V. L.; Gaskell, C. M.; Shimanovskaya, E. V. (Одеські астрономічні публікації, 2016)
We show that, contrary to simple predictions, most AGNs show at best only a small increase of lags in the J, H, K, and L bands with increasing wavelength. We suggest that a possible cause of this near simultaneity of the variability from the near-IR to the mid-IR is that the hot dust is in a hollow bi-conical outflow of which we only see the near side. Although most AGNs show near simultaneity of IR variability, there was at least one epoch when NGC 4151 showed the sharply increasing IR lag with the increase of the wavelength. This behaviour might also be present in GQ Comae. We discuss these results briefly. The relative wavelength independence of IR lags simplifies the use of IR lags for estimating cosmological parameters.